Genetic polymorphisms influencing deferasirox pharmacokinetics, efficacy, and adverse drug reactions: a systematic review and meta-analysis - Kittika Yampayon; Puree Anantachoti; Bunchai Chongmelaxme; Varalee Yodsurang; Varalee Yodsurang (Frontiers Media S.A., 2023)
Objective: Deferasirox is an iron-chelating agent prescribed to patients with iron overload. Due to the interindividual variability of deferasirox responses reported in various populations, this study aims to determine the genetic polymorphisms that influence drug responses.Methods: A systematic search was performed from inception to March 2022 on electronic databases. All studies investigating genetic associations of deferasirox in humans were included, and the outcomes of interest included pharmacokinetics, efficacy, and adverse drug reactions. Fixed- and random-effects model meta-analyses using the ratio of means (ROM) were performed.Results: Seven studies involving 367 participants were included in a meta-analysis. The results showed that subjects carrying the A allele (AG/AA) of ABCC2 rs2273697 had a 1.23-fold increase in deferasirox Cmax (ROM = 1.23; 95% confidence interval [CI]:1.06-1.43; p = 0.007) and a lower Vd (ROM = 0.48; 95% CI: 0.36-0.63; p < 0.00001), compared to those with GG. A significant attenuated area under the curve of deferasirox was observed in the subjects with UGT1A3 rs3806596 AG/GG by 1.28-fold (ROM = 0.78; 95% CI: 0.60-0.99; p = 0.04). In addition, two SNPs of CYP24A1 were also associated with the decreased Ctrough: rs2248359 CC (ROM = 0.50; 95% CI: 0.29-0.87; p = 0.01) and rs2585428 GG (ROM = 0.47; 95% CI: 0.35-0.63; p < 0.00001). Only rs2248359 CC was associated with decreased Cmin (ROM = 0.26; 95% CI: 0.08-0.93; p = 0.04), while rs2585428 GG was associated with a shorter half-life (ROM = 0.44; 95% CI: 0.23-0.83; p = 0.01).Conclusion: This research summarizes the current evidence supporting the influence of variations in genes involved with drug transporters, drug-metabolizing enzymes, and vitamin D metabolism on deferasirox responses.